The Influence of Service Quality, Destination Image, Accessibility On Tourist Satisfaction in The Botubarani Bonebolango Whale Shark Tourist Destination, Gorontalo - Mohamad, Rizki Aditya; Widawati, Ida Ayu Putri; Damayanti, Titien (Journal of Mandalika Review, 2024)
Abstract Introduction: Thisl study aimsl to investigate thel influence ofl service lquality, destinationl image, andl accessibility onl tourist lsatisfaction. Thel research was conducted atl the Whalel Shark touristl destination inl Botubarani lVillage, Bonebolango, Gorontalo. Methodology: Thisl type ofl research isl explanatory and employs a quantitative approach. Datal were collectedl directly usingl questionnaires distributedl to 381 respondents selected through purposive sampling techniques and analysed using the PLS-SEM model. Findings: The findingsl reveal thatl service qualityl has al positive andl significant effect onl tourist satisfaction, destination imagel has al positive andl significant impact onl tourists, and accessibility positivelyl andl significantlyl influencesl touristl lsatisfaction. Conclusion: Thel study conducted atl the Whalel Shark touristl destination inl Botubarani lVillage, Bonebolango, Gorontalo, examined how servicel quality, destinationl image, andl accessibility affect touristl satisfaction. Using a quantitative explanatory approach and data from 381 respondents, the findings showed that all three factors—service lquality, destinationl image, andl accessibility—positively andl significantly influence tourist satisfaction. Keywords: Service Quality, Destination Image, Accessibility, Tourist Satisfaction